Canadian Trade-Unionism Speaks Out - Chartier, Roger (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1951)
SummaryWhat is Canadian trade-unionism up to ? What are its immediate goals ? How do its long-term policies stand ? Part of these momentous questions are answered in this survey of the speeches delivered, the motions carried and the reports prepared on the occasion of the annual conventions of the three major labor bodies in Canada.